PROFIL PEMECAHAN MASALAH PADA MATERI FUNGSI SISWA KELAS VIII SMP NEGERI 4 SIGI DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT - Cindy Angeli Que Puspita; Tegoeh S. Karniman; Ibnu Hadjar (Universitas Tadulako, 2025)
The purpose of this study was to obtain a description of the problem solving profile of VIII grade students of SMP Negeri 4 Sigi in solving problems on function material in terms of cognitive style field dependent This type of research is qualitative research. The subjects in this study were two students of class VIII E SMP Negeri 4 Sigi in the school year 2023/2024 consisting of one male subject with field dependent cognitive style and one female subject with field dependent cognitive style. Data collection techniques using GEFT test, written test and interview. The results of this study are: (1) the stage of understanding the problem, the subject uses information in the form of statement sentences to identify what is known and uses information in the form of question sentences to identify what is asked, (2) the stage of planning problem solving, the subject makes a solution plan using known information and his knowledge of functions, (3) the stage of carrying out problem solving planning, the subject connects the information obtained at the stage of understanding the problem with the plan that has been made then implements the plan, (4) the stage of re-examining, the subject re-examines the solution he obtained by checking the steps of the work he made in the third stage of Polya.